Transition in microstructural and mechanical behavior by reduction of sigma-forming element content in a novel high entropy alloy. (5th May 2018) - Raza, Ahmad; Kang, Byungchul; Lee, Junho; Ryu, Ho Jin; Hong, Soon Hyung
Highlights: The mechanical alloying optimization process have been illustrated schematically specifically for high-entropy alloys. The proposed alloy systems have challenged the thermodynamic predictions and formed sigma phase. The volume fraction of sigma phase is related with the concentration of paired sigma forming elements (PSFE) content. The alloys showed higher specific yield strength and hardness as compare to previously reported high-entropy alloy systems. Graphical abstract: Unlabelled Image Abstract: A novel CrFeMoVMnx high entropy alloy (HEA) system was devised after screening done with thermodynamic constraints. The Mn content was varied (x = 0, 0.5, 1 atomic ratio), with other elements kept in equiatomic ratios, to determine the effect of paired sigma-forming element (PSFE) content on microstructural and mechanical behavior. Alloys were successfully fabricated using a powder metallurgical method after mechanical alloying (MA) for an optimized minimum milling time. The milled powder was sintered using spark plasma sintering (SPS). The microstructural analysis indicated the appearance of a σ phase in the equiatomic quinary CrFeMoVMnx system, and the volume fraction of the σ phase varied directly by Mn content. The Mn0 system exhibited the formation of a single phase solid solution. The failure of thermodynamic prediction, the role of PSFE content and Md ¯ in σ phase appearance were investigated. The transition in mechanical behavior through a reduction in Mn content was also investigated and Mn1 exhibited the highest fracture strength, of 3183 MPa, and hardness of 868 Hv, while Mn0 displayed the highest plasticity. This study demonstrates higher specific yield strength and hardness values compared to previously reported HEA systems.